2010
DOI: 10.3390/ijms11030982
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Principles of Systems Biology and Wiener's Cybernetics for Analysis of Regulation of Energy Fluxes in Muscle Cells in Vivo

Abstract: The mechanisms of regulation of respiration and energy fluxes in the cells are analyzed based on the concepts of systems biology, non-equilibrium steady state kinetics and applications of Wiener’s cybernetic principles of feedback regulation. Under physiological conditions cardiac function is governed by the Frank-Starling law and the main metabolic characteristic of cardiac muscle cells is metabolic homeostasis, when both workload and respiration rate can be changed manifold at constant intracellular level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 175 publications
(257 reference statements)
1
16
0
Order By: Relevance
“…). Thus, Cr is an efficient feedback regulator of respiration in permeabilized cardiomyocytes, as well as in skeletal oxidative m. soleus and mixed human m. vastus lateralis (Guzun & Saks ). Low apparent affinity of MtCK for Cr in these muscles (the apparent K m Cr is about 1.0–1.5 m m ) shows that low concentrations of Cr are capable to significantly increase respiration rates up to the maximal rate of ADP‐stimulated respiration (Guzun et al .…”
Section: Regulation Of Mitochondrial Respiration In Permeabilized Adumentioning
confidence: 99%
“…). Thus, Cr is an efficient feedback regulator of respiration in permeabilized cardiomyocytes, as well as in skeletal oxidative m. soleus and mixed human m. vastus lateralis (Guzun & Saks ). Low apparent affinity of MtCK for Cr in these muscles (the apparent K m Cr is about 1.0–1.5 m m ) shows that low concentrations of Cr are capable to significantly increase respiration rates up to the maximal rate of ADP‐stimulated respiration (Guzun et al .…”
Section: Regulation Of Mitochondrial Respiration In Permeabilized Adumentioning
confidence: 99%
“…To understand biological complexity, for example, in cybernetics it is long posited that behavioral robustness is the result of structural complexity (Wiener, 1965). Recent examples include metabolic networks in Escherichia coli, human hepatocytes, and erythrocytes (Behre et al, 2008), and in adult rat cardiomyocytes and human skeletal muscle (Guzun and Saks, 2010) that have been studied using this bottom-up approach. To influence biological performance, for example, it is shown that sliding mode control can be applied in a generalized bioreactor based on nonlinear model dynamics to specify appropriate nutrient flow rates, in order to achieve and maintain a desired amount of cells (Fossas et al, 2001).…”
Section: Robustness Of Cellular Networkmentioning
confidence: 99%
“…Assuming that ATP, ADP, PCr, and Cr are related through equilibrium relationships, the observation of metabolic stability was interpreted to exclude any other explanation of workload dependence of cardiac oxygen consumption than a mechanism involving the control of mitochondrial respiration by ADP or Pi only. The popular assumption of CK equilibrium, as in a mixed bag of enzymes (Wiseman and Kushmerick 1995), however, is in contradiction with the experimental evidence (Saks 2008;Guzun and Saks 2010). This includes recent high-resolution 31 P NMR experiments showing that the major part of adenine nucleotides, notably ATP in muscle cells, exists associated with macromolecules and that free ADP may be only transiently present in the cytoplasm (Nabuurs et al 2010(Nabuurs et al , 2013.…”
Section: Intracellular Energetic Units and Mitochondrial Interactosommentioning
confidence: 99%